2013
DOI: 10.1094/mpmi-07-12-0178-r
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis of Aquaporins from Desert Truffle Mycorrhizal Symbiosis Reveals a Fine-Tuned Regulation Under Drought

Abstract: We have performed the isolation, functional characterization, and expression analysis of aquaporins in roots and leaves of Helianthemum almeriense, in order to evaluate their roles in tolerance to water deficit. Five cDNAs, named HaPIP1;1, HaPIP1;2, HaPIP2;1, HaPIP2;2, and HaTIP1;1, were isolated from H. almeriense. A phylogenetic analysis of deduced proteins confirmed that they belong to the water channel proteins family. The HaPIP1;1, HaPIP2;1, and HaTIP1;1 genes encode functional water channel proteins, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 85 publications
1
48
0
Order By: Relevance
“…However, some studies have not shown positive effects of ECM fungi on aquaporin gene expression. A recent study using Helianthemum almeriense and its fungal symbiont Terfezia claveryi was conducted to investigate the expression patterns of five aquaporin genes from the plant and one from its fungal symbiont ( Navarro-Ródenas et al, 2013 ). Results of this experiment indicated that the plant aquaporin genes were not enhanced in the roots by the ECM status and were even significantly reduced in one case.…”
Section: The Role Of Mycorrhizas In Drought Resistancementioning
confidence: 99%
“…However, some studies have not shown positive effects of ECM fungi on aquaporin gene expression. A recent study using Helianthemum almeriense and its fungal symbiont Terfezia claveryi was conducted to investigate the expression patterns of five aquaporin genes from the plant and one from its fungal symbiont ( Navarro-Ródenas et al, 2013 ). Results of this experiment indicated that the plant aquaporin genes were not enhanced in the roots by the ECM status and were even significantly reduced in one case.…”
Section: The Role Of Mycorrhizas In Drought Resistancementioning
confidence: 99%
“…The studies demonstrate their strong to moderate capacity of transporting water, urea, glycerol, ammonia, and CO 2 . Their expression can be altered by mycorrhization or abiotic cues such as drought, salt, low temperature, or pH (Dietz et al, 2011;Navarro-Ródenas et al, 2012Xu et al, 2015), suggesting their multiple roles in plantfungal interactions, and their involvement in water transport and nutrient transfer of the mycorrhizal partners. Differential expressions of fungal aquaporins were also observed in a cellspecific pattern, in EcM root tips, free-living mycelium, fungal mantle, Hartig net, and fruiting body.…”
Section: Roles Of Fungal Aquaporins In Ectomycorrhizal Root Water Tramentioning
confidence: 99%
“…Secondly, the abundance and activity of fungal aquaporins could impact water availability in root extracellular space in Hartig net (Figures 1A,B). Ultimately, by changing the hydration in the apoplastic space, it can influence root aquaporin regulation and the overall root water uptake (Javot and Maurel, 2002;Marjanović et al, 2005;Lee et al, 2010;Dietz et al, 2011;Navarro-Ródenas et al, 2013;Xu et al, 2015;Calvo-Polanco et al, 2019).…”
Section: Roles Of Fungal Aquaporins In Ectomycorrhizal Root Water Tramentioning
confidence: 99%
“…In the second year, the good water status of the grapevines, the higher percentage of root colonization and lower fruit load led to considerably higher values of both A and WUE in treatment T 1 [79]. In fact, AMF are known to exert a degree of control over transpiration, allowing plants to maintain high levels of WUE [80]. Such an increase, which agrees with other studies in vines [81], may also have accounted for the enhanced growth of plants colonized with Glomus species, most probably as a result of enhanced CO 2 fixation [49].…”
Section: Discussionmentioning
confidence: 99%